Tafsir Qur'an Karim Karya Mahmud Yunus Kajian atas Karya Tafsir Nusantara - Iskandar, Iskandar (SUHUF, 2010)
The development of exegesis (tafsir) in our region began to develop since the 1960’s. It commenced with translations and commentaries that were limited to certain selected juz or surah, then continued to develop until reaching perfection and completeness. Although at the beginning he was opposed by other religious scholars, eventually the government agreed to permit his work. The work of Mahmud Yunus consequently became the first step for all Indonesian scriptual commentators to further develop the art of exegisis in the region. This paper briefly explains the Tafsir Qur'an Karim by Mahmud Yunus. Its language entails the theme of the authentification of the Qur’an verses and is an explanation and guide to its vision and orientation for all readers. As well as describing the characteristics of translation and exegesis, the paper examines the intellectual and social character of this work in the history of the development of religious commentaries in the archipelago.